Distribuição espacial da violência sexual contra crianças e adolescentes em estados brasileiros e municípios cearenses - Marques, Livia de Andrade (2016)
The objective is to investigate the Brazilian states and municipalities of greater risk for sexual violence against children and adolescents. To this end, a descriptive, observational, analytical ecological study will be carried out based on secondary data from 2014 (retrospective) on the rate of sexual violence in Brazil and the rates of abuse and sexual exploitation of the municipalities of Ceará, relating to social indicators . Part of the data was obtained through the records of sexual violence of denunciation 100 - SDH. In the analysis, the tabulation was through the Excel program and the data processed through the software STATA, version 13.0 and Arcgis, version 10. According to the data obtained, it was possible to identify that among adolescents in situations of sexual violence, (21281 / 68.2%) and in the State of Ceará (807 / 68.6%). The age range of 12 to 14 years in Brazil (9282 / 29.7%) and in Ceará (340 / 28.9%), the race / color was not reported as the majority in Brazil (12538 / 40.2% ) And in Ceará (446 / 37.9%) followed by brown (8892 / 28.5%) Brazil and Ceará 376 (376 / 31.9%). The data on the place of the rape show the victim's home as the place where sexual violence occurred in Brazil (9352 / 38.6) and Ceará (371 / 38.9%). When analyzing the spatial distribution in Brazil, we found a variation in the profile of socioeconomic development in both the states with the highest and those with the lowest rates, evidencing the occurrence of sexual violence often in states that have a good development in this perspective. This suggests the idea that it is not poverty that is related to violence, but social inequalities. As in the case of the Brazilian states, in the State of Ceará, despite an apparent good economic development in general, there is also a lack of income distribution in the municipalities of Ceará, in addition, they present correlations of indicators on vulnerabilities, health, demographic data, Development and work with sexual exploitation. These evidences require attention to policies and interventions that improve income distribution and social equality, activities aimed at adolescents and young people aimed at reducing vulnerability. In addition, a relationship between knowledge, power and violence was identified. Which refers to the need to approach with society in general along with education, the formation of ethical values ​​and citizenship, deconstruction of androcentric culture and gender discussions.